Left Ventricular Assist Device: Care On Inpatient Rehabilitation Facility. Issue 6 (November 2015) - Forrest, George; Radu, Gabriel; Rifenburg, Kathleen; Shields, Evelyn; Clift, Sarah
Abstract : Purpose: : Investigate the outcomes of patients admitted to an inpatient rehabilitation facility (IRF) after placement of a left ventricular assist device (LVAD). Design: : Retrospective review of records. Method: : Authors reviewed records of patients admitted to the IRF after cardiac surgery or admission to the hospital with either acute myocardial infarction, congestive heart failure, or placement of an LVAD. The study reports improvement in function, length of stay (LOS), and location of discharge. Findings: : The patients in the LVAD group made as much progress in terms of improvement in function as the other groups. None of the patients in the LVAD group required transfer back to medical or surgical units. All were discharged to home. Length of stay (LOS) of the LVAD group was not significantly longer than that of the other cardiac patients. Conclusions: : Patients who have had placement of an LVAD can be safely cared for in an IRF. Clinical Relevance: : This paper provides information about the indications for LVAD, the nursing care of patients with an LVAD, and the outcomes of care in an IRF.